The Evolution of the German-Chinese Strategic Partnership: A Case Study Approach - Ehret, Marian (Animo Repository, 2019)
This paper examined current and future tendencies in the evolution of the German-Chinese strategic partnership. Because of current events, both countries acted increasingly aligned. The central research question is: will the strategic partnership between China and Germany supersede the American-German alliance regarding political importance? A literature review and a media content analysis in a German context, focusing on the years from 2013 until 2018, showed that German scholars and publishers evaluated the direction and potential of the binational relations as (mostly) positive. As their judgment came from a short-term observation, Oswald Spengler’s culture-historical approach was applied, as it allowed embedding the evolution of the strategic partnership into a profound long-term perspective. Spengler’s work had been criticized by older scholars because of its macroscopic ambitions and Spengler’s political statements, but now experienced a renaissance because of its usefulness for explaining unexpected current developments. A survey, as a verification attempt, was conducted during the HES conference in Germany with attending scholars, which showed that many of them shared the criticism. The future foreign relations of Western powers, which were relevant in the context of this study, yielded higher than average approval rating. Spengler’s work was carefully applied to the topic and helped to arrive at negative results concerning the status of Germany’s and China’s future relations. These findings were opposed to the earlier ones from the literature review and media content analysis. Despite some aspects that Spengler predicted wrongly, his model turned out to be useful overall. The findings stated that the process of deeper Western integration and unification under American leadership would prevent a German-Chinese strategic partnership from arriving at a level of significance, which could seriously rival the status of Germany’s relations with America. This study demonstrated the importance of using a long-term prognostic model, as it could yield very different but more relevant results than a short-term observation. Spengler’s model helped to arrive at findings of major significance for the future of the Western world and its relations to China.